Hubungan antara Anonimitas dan Moral Disengagement dengan Perilaku Cyberbullying pada Penggemar K-Pop yang Melakukan Fanwar - Khoiriyah, Erfira; Pramono, Ridwan Budi (Universitas Muria Kudus, 2023)
This study is a quantitative study that aims to determine the relationship between anonymity and moral disengagement with cyberbullying behavior in K-Pop fans who do fanwar. Purposive sampling was used in sampling so that 250 K-Pop fans filled out the cyberbullying scale, anonymity scale, and moral disengagement scale. The results of the analysis show that there is a relationship between anonymity and moral disengagement with cyberbullying behavior in K-pop fans who do fanwar with a correlation coefficient of 0.413 and a p value 0.001 (p 0.01) and an effective contribution of 17%. Anonymity is positively and significantly related to cyberbullying as indicated by a correlation coefficient of 0.271 and a p value of 0.001 (p 0.01). Moral disengagement is positively and significantly related to cyberbullying as indicated by a correlation coefficient of 0.398 and a p value of 0.001 (p 0.01). The results indicate that anonymity and moral disengagement can increase individual participation in cyberbullying behavior. Structural Equation Modeling (SEM) analysis was conducted to assess the strength of aspects. The aspect of